A multiplex PCR for the identification of Echinococcus multilocularis, E. granulosus sensu stricto and E. canadensis that infect human. Issue 12 (31st July 2019) - Chen, Fan; Liu, Lei; He, Qili; Huang, Yan; Wang, Wentao; Zhou, Guo; Yu, Wenjie; He, Wei; Wang, Qi; Zhang, Guangjia; Liao, Sha; Li, Ruirui; et al.
Abstract: Echinococcus granulosus sensu stricto ( s.s. ), Echinococcus multilocularis and Echinococcus canadensis are the common causes of human echinococcosis in China. An accurate species identification tool for human echinococcosis is needed as the treatments and prognosis are different among species. The present work demonstrates a method for the simultaneous detection of these three Echinococcus species based on multiplex polymerase chain reaction (mPCR). Specific primers of this mPCR were designed based on the mitochondrial genes and determined by extensive tests. The method can successfully detect either separated or mixed target species, and generate expected amplicons of distinct size for each species. Sensitivity of the method was tested by serially diluted DNA, showing a detection threshold as less as 0.32 pg for both E. granulosus s.s. and E. canadensis, and 1.6 pg for E. multilocularis . Specificity assessed against 18 other parasites was found to be 100% except weakly cross-react with E. shiquicus . The assay was additionally applied to 69 echinococcosis patients and 38 healthy persons, confirming the high reliability of the method. Thus, the mPCR described here has high application potential for clinical identification purposes, and can further provide a useful tool for evaluation of serology and imaging method.